Method for manufacturing conductive polymer dispersion and method for manufacturing solid electrolytic capacitor

JP2025041203APending Publication Date: 2025-03-26NIPPON CHEMI CON CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023148353
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、低等価直列抵抗の固体電解コンデンサを実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025041203000001_ABST
    Figure 2025041203000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a conductive polymer dispersion for manufacturing a solid electrolytic capacitor having a low equivalent-series resistance, a method for manufacturing a solid electrolytic capacitor having a low equivalent-series resistance, and a method for manufacturing a conductive polymer dispersion.SOLUTION: A method for manufacturing a conductive polymer dispersion includes a polymerization step of polymerizing 2-ethyl-3,4-ethylenedioxythiophene in a liquid containing polystyrene sulfonic acid. In this polymerization step, a liquid temperature during polymerization should be kept between 0°C or higher and 15°C or lower. Solid electrolytic capacitors are manufactured by forming a solid electrolytic layer between an anode body and a cathode body using the conductive polymer dispersion obtained by the manufacturing method.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a conductive polymer dispersion for forming a solid electrolyte of a solid electrolytic capacitor, and a method for producing a solid electrolytic capacitor. [Background technology]

[0002] An electrolytic capacitor has anode and cathode foils made of valve metals such as tantalum or aluminum. The anode foil is enlarged by forming the valve metal into a sintered or etched foil, and the enlarged surface is coated with a dielectric film by anodizing or other treatment. An electrolyte is interposed between the anode and cathode foils.

[0003] Electrolytic capacitors have the advantage that they can easily obtain a large capacitance compared to other types of capacitors because the specific surface area can be increased by expanding the surface area of ​​the anode foil. Electrolytic capacitors contain electrolyte in the form of an electrolyte solution. The contact area of ​​the electrolyte solution with the dielectric film of the anode foil increases. This makes it easier to further increase the capacitance of electrolytic capacitors.

[0004] In recent years, solid electrolytic capacitors, which use a solid electrolyte with higher conductivity than the electrolyte, have also been attracting attention. Solid electrolytic capacitors use a solid electrolyte with higher conductivity than the electrolyte, and can achieve low equivalent series resistance (ESR). Manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes are known as solid electrolytes.

[0005] In addition, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has excellent adhesion to dielectric films, are rapidly becoming popular as solid electrolytes. Conductive polymers use acid compounds such as polyanions as dopants to develop high conductivity. Therefore, solid electrolytic capacitors have the advantage of low equivalent series resistance (ESR).

[0006] A solid electrolyte containing a conductive polymer is formed by applying or impregnating a conductive polymer dispersion between an anode body and a cathode body and drying the dispersion medium. The conductive polymer dispersion is a dispersion of a conductive polymer, and for example, water is used as the dispersion medium to disperse the conductive polymer in water. The conductive polymer is produced by mixing a monomer, which becomes a monomer unit of the conductive polymer, a dopant, and an oxidizing agent, and subjecting the mixture to chemical oxidative polymerization. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2011-60980 A [Patent Document 2] JP 2014-152320 A Summary of the Invention [Problem to be solved by the invention]

[0008] Such solid electrolytic capacitors are, for example, a main component of a power converter, and are incorporated within the power converter as a component of a voltage smoothing circuit. In recent years, power converters have increasingly adopted MOSFETs (Metal Oxide Semiconductor Field Effect Transistors) and IGBTs (Insulated Gate Bipolar Transistors) as power semiconductors. Power converters using these wide band gap semiconductors have lower on-resistance, faster switching operations, and higher efficiency due to reduced power loss, compared to conventional power converters using silicon.

[0009] Solid electrolytic capacitors are closely related to the miniaturization or high efficiency of power converters. Solid electrolytic capacitors are affected by equivalent series resistance (ESR), which limits the allowable ripple current. When solid electrolytic capacitors are used in the voltage smoothing circuit of a power converter, many solid electrolytic capacitors are connected in parallel to handle the ripple current. Therefore, in order to further miniaturize power converters, electrolytic capacitors with lower equivalent series resistance are required.

[0010] Such a solid electrolytic capacitor with a lower equivalent series resistance is desired not only in the field of power converters, but also in other fields as well. The present invention has been proposed in order to solve the above-mentioned problems, and an object of the present invention is to provide a method for producing a solid electrolytic capacitor with a low equivalent series resistance, and a method for producing a conductive polymer dispersion. [Means for solving the problem]

[0011] In order to solve the above problems, the method for producing a conductive polymer dispersion liquid of the present embodiment includes a polymerization step of polymerizing 2-ethyl-3,4-ethylenedioxythiophene in a liquid in the presence of polystyrene sulfonic acid, and in the polymerization step, the liquid temperature during polymerization is 0° C. or higher and 15° C. or lower.

[0012] In the polymerization step, the liquid temperature during polymerization may be set to 5°C or higher and 15°C or lower.

[0013] The method may further include a step of adjusting the pH of the dispersion liquid obtained through the polymerization step and having the conductive polymer dispersed therein to a value of 3 or more and 6 or less.

[0014] Another aspect of the present invention is a method for producing a solid electrolytic capacitor, comprising forming a solid electrolyte layer between an anode body and a cathode body using the conductive polymer dispersion obtained by this production method. Effect of the Invention

[0015] According to the present invention, a solid electrolytic capacitor with a low equivalent series resistance can be realized. [Brief description of the drawings]

[0016] [Figure 1] 1 is a graph in which the horizontal axis represents the polymerization temperature and the vertical axis represents the electrical conductivity of the solid electrolyte layer. [Diagram 2] 1 is a graph in which the horizontal axis represents polymerization temperature and the vertical axis represents equivalent series resistance and yield of the solid electrolytic capacitor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The following describes embodiments of the present invention. However, the present invention is not limited to the embodiments described below.

[0018] (Conductive polymer dispersion) A conductive polymer dispersion is a dispersion in which a conductive polymer is dispersed in a dispersion medium. The conductive polymer dispersion is used to form a solid electrolyte layer in a solid electrolytic capacitor. A solid electrolyte layer containing the conductive polymer is formed by volatilizing the dispersion medium of the conductive polymer dispersion by drying.

[0019] The conductive polymer is polyethylated ethylenedioxythiophene (hereinafter referred to as Et-PEDOT) doped with polystyrene sulfonic acid (hereinafter referred to as PSS). Et-PEDOT is a polymer with ethylated ethylenedioxythiophene (hereinafter referred to as Et-EDOT) as a monomer unit. Ethylated ethylenedioxythiophene is 2-ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine, in which an ethyl group is added to 3,4-ethylenedioxythiophene.

[0020] The dispersion medium of the conductive polymer dispersion may be any medium in which the particles or powder of Et-PEDOT doped with PSS can be dispersed. The dispersion medium is typically water, but may also be an organic solvent or a mixture of an organic solvent and water. Examples of organic solvents include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds.

[0021] Examples of polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. Examples of alcohols include methanol, ethanol, propanol, and butanol. Examples of esters include ethyl acetate, propyl acetate, and butyl acetate. Examples of hydrocarbons include hexane, heptane, benzene, toluene, and xylene. Examples of carbonate compounds include ethylene carbonate and propylene carbonate. Examples of ether compounds include dioxane and diethyl ether. Examples of chain ethers include ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether. Examples of heterocyclic compounds include 3-methyl-2-oxazolidinone. Examples of nitrile compounds include acetonitrile, glutarodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile.

[0022] The conductive polymer dispersion may contain additives such as polyhydric alcohols. Examples of polyhydric alcohols include polyethylene glycol, 1-hexanol, ethylene glycol, diethylene glycol, triethylene glycol, or a combination of two or more of these. Since polyhydric alcohols have a high boiling point, they remain in the solid electrolyte layer even after the conductive polymer dispersion is dried. Furthermore, the conductive polymer dispersion may contain other compounds. The other compounds are, for example, conventional additives such as organic binders, surfactants, antifoaming agents, coupling agents, antioxidants, and ultraviolet absorbers.

[0023] In this conductive polymer dispersion, the conductive polymer is produced by a polymerization process. In the polymerization process, the monomer Et-EDOT, the dopant PSS, and an oxidant are mixed and stirred until chemical oxidation polymerization is completed. After the polymerization process, residual monomers and impurities are removed by purification means such as ultrafiltration, cation exchange, and anion exchange. This results in a conductive polymer dispersion. The conductive polymer is dispersed using, for example, ultrasound. In the polymerization process, an acid or its alkali metal salt that releases PSS may be mixed in place of PSS.

[0024] It is preferable that Et-EDOT is added to the conductive polymer dispersion at a concentration of 1 mM or more and 6.25 mM or less. In this range, the conductive polymer is less likely to aggregate. In addition, in this range, the heat resistance is improved, and even if the solid electrolyte layer is exposed to a high-temperature environment, the deterioration of various characteristics of the solid electrolytic capacitor is suppressed.

[0025] The number average molecular weight of the PSS is 1,000 to 2,000,000, and preferably 10,000 to 500,000. If the number average molecular weight is less than 1,000, the conductivity of the resulting conductive polymer is insufficient and dispersibility is reduced, which is not preferred, whereas if the number average molecular weight exceeds 2,000,000, the viscosity of the mixture increases, which is not preferred.

[0026] The oxidizing agent is preferably an iron salt of an inorganic acid or an organic acid, or a persulfate. For example, ferric chloride hexahydrate, anhydrous ferric chloride, ferric nitrate nonahydrate, ferric nitrate, ferrous sulfate, ferric sulfate, ferric sulfate n-hydrate, ferric ammonium sulfate dodecahydrate, ferric perchlorate n-hydrate, ferric tetrafluoroborate, cupric chloride, cupric sulfate, cupric tetrafluoroborate, nitrosonium tetrafluoroborate, ammonium persulfate, sodium persulfate, potassium persulfate, potassium periodate, hydrogen peroxide, ozone, potassium ferric hexacyano, tetraammonium cerium (IV) sulfate dihydrate, bromine, iodine, ferric dodecylbenzenesulfonate, ferric paratoluenesulfonate, ferric naphthalenesulfonate, ferric anthraquinonesulfonate, periodic acid, iodic acid, etc. may be used as the oxidizing agent, or a single compound may be used as the oxidizing agent, or two or more compounds may be used as the oxidizing agent.

[0027] In particular, it is preferable to use an iron salt such as ferrous sulfate in combination with a peroxodisulfate as the oxidizing agent. The iron salt serves as an oxidation initiator and catalyst, and the peroxodisulfate serves as an oxidation promoter. That is, the divalent iron ion of the oxidizing agent reacts with the persulfate ion to form radical sulfate ions, and the oxidation reaction of the monomer is promoted by the radical sulfate ions. The divalent iron ion reacting with the persulfate ion becomes a trivalent iron ion, oxidizes the monomer, returns to a divalent iron ion, and reacts with the persulfate ion again, repeating this cycle. It is preferable to adjust the pH of the polymerization solution to the acidic side by adding sulfuric acid or the like. For example, the polymerization reaction is promoted by adjusting the polymerization solution to the acidic side, such as pH=1.9.

[0028] The liquid temperature during polymerization is maintained between 0°C and 15°C. This reduces the equivalent series resistance of the solid electrolytic capacitor. Although this is speculation and not limited to this, it is believed that when the liquid temperature during polymerization is around 10°C, the conductivity of the solid electrolyte layer increases, and therefore the equivalent series resistance of the solid electrolytic capacitor decreases. Figure 1 is a graph with the polymerization temperature on the horizontal axis and the conductivity of the solid electrolyte layer on the vertical axis. As shown in Figure 1, when the polymerization liquid temperature is 10°C, the conductivity peaks.

[0029] Preferably, the liquid temperature during polymerization is 5°C or higher and 15°C or lower. When a conductive polymer dispersion polymerized at a liquid temperature of 0°C is used, the equivalent series resistance of the solid electrolytic capacitor is further reduced compared to the range of 5°C or higher and 15°C or lower. However, compared to the case of polymerization at a liquid temperature of 0°C, polymerization proceeds well at a liquid temperature of 5°C or higher and 15°C or lower, and PSS is efficiently doped into Et-PEDOT. That is, when polymerization is performed at a liquid temperature of 5°C or higher and 15°C or lower, the yield of Et-PEDOT doped with PSS is improved.

[0030] When concentrating the conductive polymer dispersion, it is preferable to adjust the pH of the conductive polymer dispersion after the polymerization reaction to 3 or more and 6 or less. If the pH is 3 or more and 6 or less, even if the concentration of Et-PEDOT doped with PSS is increased, it is difficult for it to aggregate in the conductive polymer dispersion. In this pH adjustment step, for example, an aqueous ammonia solution may be dropped into the conductive polymer dispersion. The concentration step is, for example, ultrafiltration, in which the conductive polymer dispersion is passed through a semipermeable membrane by pressure or the like.

[0031] (Solid electrolytic capacitor) A solid electrolytic capacitor is a passive element that stores and discharges electric charge by electrostatic capacitance. In this solid electrolytic capacitor, an anode body and a cathode body on which a dielectric film is formed face each other, and a solid electrolyte layer is interposed between the anode body and the cathode body. The solid electrolytic capacitor may include an electrolytic solution in addition to the solid electrolyte layer. A separator may be inserted between the anode body and the cathode body to prevent short circuits between the anode body and the cathode body and to maintain the solid electrolyte layer.

[0032] The solid electrolyte layer includes a conductive polymer in a conductive polymer dispersion. The conductive polymer is attached between the anode body and the cathode body by immersing each of the anode body, the cathode body, and the separator in the conductive polymer dispersion and drying them. Alternatively, the conductive polymer may be attached by producing a capacitor element by winding or stacking the anode body and the cathode body with the separator interposed therebetween, and then immersing the capacitor element in the conductive polymer dispersion and drying it. In addition to immersion, the conductive polymer dispersion may be applied by drop coating or spray coating. The drying step may be repeated multiple times, and drying may be performed under reduced pressure.

[0033] The anode and cathode bodies are alternately stacked with a separator sandwiched therebetween in a stacked arrangement. In the stacked arrangement, the capacitor elements may be flat-plate type without an exterior, or may be sealed by, for example, covering the capacitor elements with a laminate film, or by molding, dip-coating, or printing with a resin such as a heat-resistant resin or an insulating resin.

[0034] Alternatively, the anode body and the cathode body are wound in a wound arrangement in which they are alternately stacked with a separator sandwiched therebetween. In the wound arrangement, for example, the capacitor element is inserted into a cylindrical exterior case with a bottom, and the open end of the exterior case is sealed with a sealing body by crimping. The sealing body is made of, for example, rubber, or a laminate of rubber and a hard substrate. Examples of rubber include ethylene propylene rubber and butyl rubber.

[0035] The anode body and the cathode body are foils made of valve metal. Valve metals include aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. The purity of the anode body is preferably 99.9% or more, and that of the cathode body is preferably 99% or more, but impurities such as silicon, iron, copper, magnesium, and zinc may be included. In addition, when the solid electrolytic capacitor is a flat type, a solid electrolyte layer may be formed on the anode body so as to cover the dielectric film, and then a metal paste such as silver paste may be printed and dried. This silver layer corresponds to the cathode of the solid electrolytic capacitor.

[0036] The anode body has a porous structure on the surface as a sintered body obtained by sintering a valve metal powder or an etched foil obtained by etching a stretched foil. The porous structure is composed of tunnel-like pits, spongy pits, or voids between densely packed powder particles. The porous structure is typically formed by direct current etching or alternating current etching in an acidic aqueous solution containing halogen ions such as hydrochloric acid, or by vapor deposition or sintering metal particles or the like on the core. The cathode body may also have a porous structure on the surface as necessary.

[0037] The dielectric film is the dielectric layer of a solid electrolytic capacitor, and is typically an oxide film formed on the surface of an anode body. If the anode body is an aluminum foil, the dielectric film is an aluminum oxide layer obtained by oxidizing the porous structure region. This dielectric film is formed by applying a voltage in a solution that does not contain halogen ions, such as an aqueous solution of adipic acid or boric acid. The cathode body may also be formed with a dielectric film as necessary, and may further include a layer of metal nitride, metal carbide, or metal carbonitride formed by vapor deposition, or one containing carbon on the surface.

[0038] Examples of the separator include cellulose papers such as kraft, Manila hemp, esparto, hemp, and rayon, and mixed papers thereof; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins. These resins can be used alone or in combination.

[0039] The solvent of the electrolyte is not particularly limited, but a protonic organic polar solvent or an aprotic organic polar solvent can be used. As the protonic polar solvent, monohydric alcohols, polyhydric alcohols, oxyalcohol compounds, etc. are typified, such as ethylene glycol or propylene glycol. As the aprotic polar solvent, sulfones, amides, lactones, cyclic amides, nitriles, sulfoxides, etc. are typified, such as sulfolane, γ-butyrolactone, ethylene carbonate, or propylene carbonate.

[0040] The solute contained in the electrolytic solution includes anion and cation components, and is typically an organic acid such as adipic acid or benzoic acid or its salt, an inorganic acid such as boric acid or phosphoric acid or its salt, or a complex compound of an organic acid such as borodisalicylic acid and an inorganic acid or its ion-dissociable salt, and is used alone or in combination of two or more. Examples of the salts of these organic acids, salts of inorganic acids, and at least one salt of a complex compound of an organic acid and an inorganic acid include ammonium salts, quaternary ammonium salts, quaternary amidinium salts, amine salts, sodium salts, potassium salts, etc. An acid that becomes an anion and a base that becomes a cation may be added separately to the electrolytic solution as solute components. EXAMPLES

[0041] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0042] (Examples 1 to 4) Each conductive polymer dispersion was prepared by the manufacturing methods of Examples 1 to 4 and Comparative Examples 1 and 2. The manufacturing methods of Examples 1 to 4 and Comparative Examples 1 and 2 are common to the following points. First, 73.798 g of PSS, which is a dopant, was added to 879.619 mL of pure water. 18.775 g of ferrous sulfate, which is an oxidizing agent and has the composition formula FeSO4, was added to this PSS aqueous solution, and 122.061 g of sulfuric acid, which has the chemical formula H2SO4, was added to adjust the pH.

[0043] The mixture was stirred with a stirrer and dissolved oxygen was removed by nitrogen bubbling. The mixture was then stirred with a homogenizer for 2 hours. 5.747 g of the monomer Et-EDOT was added to the mixture, and the mixture was homogenized and stirred with a stirrer for 30 minutes. The amount of PSS and Et-EDOT mixed was adjusted so that the molar ratio of PSS was twice that of Et-EDOT.

[0044] Next, an aqueous solution of 15.408 g of ammonium peroxodisulfate, an oxidizing agent with the molecular formula (NH4)S2O8, dissolved in 84.592 mL of pure water was further mixed into the mixture to initiate polymerization.

[0045] During the polymerization, the mixed liquid was maintained at each polymerization temperature corresponding to Examples 1 to 4 and Comparative Examples 1 and 2. The polymerization temperature in Example 1 was 0° C., the polymerization temperature in Example 2 was 5° C., the polymerization temperature in Example 3 was 10° C., the polymerization temperature in Example 4 was 15° C., the polymerization temperature in Comparative Example 1 was 20° C., and the polymerization temperature in Comparative Example 2 was 30° C. The polymerization time was 24 hours, and homogenizer treatment and stirring with a stirrer were continued during the polymerization.

[0046] After 24 hours, ion exchange resin was added to the mixture and stirred for another 24 hours. The ion exchange resin was then removed from the mixture and ultrafiltered to remove the remaining monomer, dopant, and oxidant. After ion exchange and ultrafiltering, the conductive polymer particles were refined using a high-pressure homogenizer.

[0047] In this way, the conductive polymer dispersions of Examples 1 to 4 and Comparative Examples 1 and 2 were produced. In the course of this manufacturing method, the yields of Examples 1 to 4 and Comparative Examples 1 and 2 due to differences in polymerization temperature were calculated. When calculating the yield, the conductive polymer liquid was evaporated, and the remaining solid content was weighed as Et-PEDOT:PSS obtained after synthesis. The yield was calculated by dividing the weight of this remaining solid content by the total weight of Et-EDOT and PSS added when preparing the conductive polymer dispersion, and multiplying it by 100 to convert it into a percentage.

[0048] (ESR test) Solid electrolytic capacitors were produced using the conductive polymer dispersions of Examples 1 to 4 and Comparative Examples 1 and 2. The conductive polymer dispersions of Examples 1 to 4 and Comparative Examples 1 and 2 were adjusted to pH 4 by adding ammonia. Furthermore, these conductive polymer dispersions were added with 10 wt % ethylene glycol relative to the conductive polymer dispersion, and 85 wt % sorbitol relative to the solid content, i.e., the total weight of the conductive polymer and sorbitol.

[0049] The anode body is an aluminum foil with a purity of 99.99%. The surface of this aluminum foil was enlarged by DC etching. A dielectric film of aluminum oxide was formed on the enlarged aluminum foil by chemical conversion treatment. In the chemical conversion treatment, the anode was immersed in an aqueous boric acid solution and a voltage was applied while a constant current was passed through it. The voltage was applied until the chemical conversion voltage reached 946V.

[0050] An insulating resist layer was printed on the anode body except for the region to be the anode, and the anode body was dried. After printing the insulating resist layer, the anode body was immersed in the conductive polymer dispersion liquid of Examples 1 to 4 and Comparative Examples 1 and 2, and the conductive polymer was attached to the dielectric film. After the anode body was pulled out of the conductive polymer dispersion liquid, the anode body was left to stand for 10 minutes in a temperature environment of 60°C, and further left to stand for 30 minutes in a temperature environment of 110°C. In this way, the anode body was dried, and a solid electrolyte layer of the conductive polymer was formed on the anode body.

[0051] After the solid electrolyte layer was formed, carbon paste was applied onto the solid electrolyte layer and allowed to harden by leaving it in a 110°C environment for 30 minutes. Furthermore, silver paste was applied onto the carbon layer and copper foil was attached as a lead terminal at the same time. The silver paste was allowed to harden by leaving it in a 110°C environment for 30 minutes with the copper foil attached to the silver paste before hardening. The above carbon layer, silver layer, and copper foil layer correspond to the cathode body of the solid electrolytic capacitor.

[0052] The equivalent series resistance of these solid electrolytic capacitors was measured. The equivalent series resistance was measured at room temperature using an LCR meter (model number ZM2376, manufactured by NF Corporation). The measurement frequency was 100 kHz, the DC bias was 1.5 V, and the AC current level was a sine wave of 1.0 Vms.

[0053] Table 1 below shows the equivalent series resistance (Ω) at 100 kHz, together with the polymerization temperature (°C) and yield, of the solid electrolytic capacitors produced using the conductive polymer dispersions of Examples 1 to 4 and Comparative Examples 1 and 2. Six solid electrolytic capacitors were produced each, and the equivalent series resistance value is the average value of three capacitors.

[0054] (Table 1) TIFF2025041203000002.tif71161

[0055] Further, a graph showing the relationship between the polymerization temperature and the equivalent series resistance and the relationship between the polymerization temperature and the yield was created based on Table 1. In Fig. 2, the horizontal axis is the polymerization temperature, the vertical axis is the equivalent series resistance and the yield, the solid black plots are the equivalent series resistance, and the open white plots are the yield.

[0056] 1, it was confirmed that the equivalent series resistance of Examples 1 to 4 in which the polymerization temperature was in the range of 0° C. or more and 15° C. or less was reduced by 25% or more compared to Comparative Examples 1 and 2. Furthermore, it was confirmed that the yield of Examples 2 to 4 in which the polymerization temperature was in the range of 5° C. or more and 15° C. or less was improved from 53% to 59% compared to 27% in Example 1.

[0057] In this way, the polymerization process includes polymerizing Et-EDOT in a liquid containing PSS, and the equivalent series resistance of the solid electrolytic capacitor is improved by setting the liquid temperature during polymerization to between 0°C and 15°C in the polymerization process. Furthermore, the yield of the conductive polymer is improved by setting the liquid temperature during polymerization to between 5°C and 15°C in the polymerization process.

Claims

1. The method includes a polymerization step of polymerizing 2-ethyl-3,4-ethylenedioxythiophene in a liquid in which polystyrene sulfonic acid is present, In the polymerization step, the liquid temperature during polymerization is 0° C. or higher and 15° C. or lower. A method for producing a conductive polymer dispersion, comprising:

2. In the polymerization step, the liquid temperature during polymerization is 5° C. or higher and 15° C. or lower.

2. A method for producing the conductive polymer dispersion according to claim 1,

3. The method further comprises a step of adjusting the pH of the dispersion liquid obtained through the polymerization step and having the conductive polymer dispersed therein to a pH of 3 or more and 6 or less.

2. A method for producing the conductive polymer dispersion according to claim 1,

4. forming a solid electrolyte layer between an anode body and a cathode body using the conductive polymer dispersion obtained by the manufacturing method according to any one of claims 1 to 3; A method for producing a solid electrolytic capacitor comprising the steps of:

Citation Information

Patent Citations

  • Solid electrolytic capacitor

    JP2011060980A

  • Electroconductive polymer-containing coating material for forming a transparent electroconductive pattern, transparent electroconductive pattern-formed object, and method for manufacturing the same

    JP2014152320A